Cost-Effectiveness Analysis of Rifampicin and Bedaquiline Use for Tuberculosis Treatment: A Systematic Review - wawang anwarudin (Universitas Muhammadiyah Purwokerto, 2026)
Introduction: Multidrug-resistant tuberculosis (MDR-TB), particularly rifampicin-resistant tuberculosis (RR-TB), remains a major challenge to global tuberculosis control and imposes substantial economic burdens on healthcare systems. Since 2020, the World Health Organization (WHO) has recommended the use of bedaquiline, a novel oral anti-tuberculosis drug, as part of an all-oral shorter regimen for the treatment of MDR-TB. This recommendation aims to improve treatment outcomes while reducing treatment duration and toxicity associated with conventional regimens. Materials and Methods: This study employed a systematic review approach of peer-reviewed articles published between 2020 and 2026. A total of 14 studies were included in the analysis. The selected studies evaluated cost-effectiveness outcomes such as direct medical costs, quality-adjusted life years (QALYs), and incremental cost-effectiveness ratios (ICERs). Various pharmacoeconomic modeling methods were applied in the included studies, including Markov models, decision tree analyses, and randomized controlled trials. Result: Most of the reviewed studies reported that bedaquiline-based regimens are more cost-effective compared with conventional rifampicin-based therapy. The ICER values were generally below the national willingness to pay thresholds, indicating favorable economic value. In several studies, bedaquiline-based regimens even demonstrated cost-saving potential. In particular, the BPaL regimen (bedaquiline, pretomanid, and linezolid) showed shorter treatment duration, improved clinical outcomes, and lower relapse and resistance rates. Conclusion: Bedaquiline represents a clinically effective and economically efficient treatment option for MDR-TB. Its implementation should be prioritized in national tuberculosis control programs, especially in low and middle income countries with a high TB burden. Further real-world implementation studies are necessary to support broader integration into healthcare systems. Keywords: Bedaquiline, cost-effectiveness, MDR-TB, rifampicin, ICER